Entrepreneurial Leadership Practice Through Mini-Project: Participatory Action Research (PAR) at the School of Tourism - Ivan Suaidi; Whidya Utami; Liliana Dewi (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
This research aimed to explore the implementation of entrepreneurial leadership through mini-projects in a tourism sub-marketing context and to assess the performance of tourism students in designing tourism products using this approach. To mitigate these challenges, the research proposed a Participatory Action Research (PAR) methodology was employed. A single third-semester sub-marketing class was the focus. Purposive sampling was used to select participants aligned with the research theme. Data collection involved student and lecturer interviews. Mini projects included article reviews and project presentations. The research results are that teaching entrepreneurial leadership through mini-projects is successfully conducted for three days: 1) introduction to topics containing basic marketing concepts, 2) the importance of why people apply for marketing activities, and 3) strategies to win the markets. The activity was filled with reviewing articles on the second day, and discussions were completed with project presentations on the third day. Additionally, the conclusion of the research is that the student's performance is very positive, measured by indicators of directness in stating ideas, product novelty, and received responses.